Estimating the medical cost for motor vehicle accident - Muhammad Mujahid Ismail; Noriza Majid (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study is to investigate the relationship between the cost of road accident treatment at Hospital Canselor Tuanku Muhriz and factors such as gender, age group, vehicle type, injury type, duration of stay in hospital and severity. The data used were population data collected at the hospital Emergency Department for a period of one year from 2007 to 2008. A total of 543 road accident patients were taken for this study but only 507 patients were used for analysis. The analyses used in this study were divided into two, namely descriptive analysis and multiple regression analysis. The results of the study show three independent variables i.e. the period of hospitalization, injury type and severity provide significant p-value and t-value to the cost of road accident patients. The methodology from this study can be used in related future research.